ANALISIS DRAMA MASTODON DAN BURUNG KONDOR KARYA W.S. RENDRA MENGGUNAKAN PENDEKATAN STRUKTURALISME GENETIK LUCIEN GOLDMANN - Dina Alistri; Mya Mulyany; Nazwa Agnia Teja Respati; Rista Septiwianti Septiwianti; Roby Rahmat Kausar; Tri Handoyo; Adita Widara Putra (Jurnal Bastra (Bahasa dan Sastra), 2025)
Drama is a type of literary work that has a distinctive characteristic, namely combining literary elements and performing arts. This study analyzed the drama "Mastodon and Condor" written by W.S. Rendra using the genetic structuralism approach introduced by Lucien Goldmann. This approach was chosen because it is suitable to show how this drama depicts humanitarian issues, the author's views, and social groups in the context of Indonesia during the New Order period. This analysis uses key concepts from Lucien Goldmann's theory of genetic structuralism, with a focus on the fact of humanity, the author's worldview, and the collective group. The results of the study show that this drama not only features dramatic conflict, but also provides philosophical, moral, and spiritual reflections on the fate of humans in an oppressive system. This drama also reflects the socio-historical dynamics of society and becomes a means of criticism that arouses collective consciousness.